2019
DOI: 10.3390/ijerph17010258
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos, Smoking and Lung Cancer: An Update

Abstract: This review updates the scientific literature concerning asbestos and lung cancer, emphasizing cumulative exposure and synergism between asbestos exposure and tobacco smoke, and proposes an evidence-based and equitable approach to compensation for asbestos-related lung cancer cases. This update is based on several earlier reviews written by the second and third authors on asbestos and lung cancer since 1995. We reevaluated the peer-reviewed epidemiologic studies. In addition, selected in vivo and in vitro anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 106 publications
(147 reference statements)
2
66
1
8
Order By: Relevance
“…It is known that tobacco smoking is linked to the occurrence of lung cancer (Klebe et al, 2019 ). In our subgroup analysis, we found that high SNRPA expression was correlated with a poor clinical prognosis of both smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that tobacco smoking is linked to the occurrence of lung cancer (Klebe et al, 2019 ). In our subgroup analysis, we found that high SNRPA expression was correlated with a poor clinical prognosis of both smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Die Dosishäufigkeitsbeziehungen von 25 Faserjahren für die Lungenkrebsmortalität sind aufgrund insgesamt 14 Studien abgeleitet worden. Neuere Untersuchungen sprechen dafür, dass die Verdopplungsdosis für den asbestbedingten Lungenkrebs deutlicher niedriger, nämlich in einem Bereich von etwa 4 -5 Faserjahren anzunehmen ist [19,20]. Dies ist aber ohne eine Änderung der Legaldefinition zur BK Nr.…”
Section: Zur Haftungsbegründenden Kausalitätunclassified
“…Iz ovog razloga je SZO pušenje uvrstilo u bolest zavisnosti zajedno sa alkoholizmom i narkomanijom i šifrirala oznakom F17 u Međunarodnoj klasifikaciji bolesti, MKB-10 [2,3]. Noviji radovi potvrđuju uzročnu povezanost pušenja i karcinoma pluća, karcinoma bronha, infarkta miokarda i hronične opstruktivne bolesti pluća [4][5][6].…”
Section: Uvodunclassified